The role of affectivity in the relationship between teacher and student and its implications in learning - de Medeiros, Maria Fabrícia (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
The present work had as general objective to verify if the relations between teacher and student in the daily life of the classroom influence in the process of teaching and learning. We seek to elencar, theoretical and methodological reflections on the actions and means used by schools in the work with the theme of affectivity, teaching and learning and the teacher's attitude regarding the valuation of affectivity in their practice and experience in the classroom. The theoretical framework was based on the studies and reflections of authors who bring reflections about the affective question, being this primordial in the construction of human relations, as well as discussions of the relationships that take place within the school environment and influence the construction of the identity, autonomy and learning of the Students. However, working effectively with such a deep theme enabled us to perceive that affectivity is directly linked to teaching and learning. Despite the difficulties encountered regarding the coexistence between individuals and their differences, it is possible to develop a school education based on effective affective actions, promoting autonomy and the overall development of students. Today, it is necessary to deepen and work on the affective question, since the primordial values have been left aside in human relations. Based on this premise, a bibliographical research was carried out in which sources such as: books, periodicals, abstracts, articles, monographs, dissertations and theses were used.